Non-Newtonian pulsatile flow through an artery with two stenosis. (2021) - Kumar, Gaurav; Kumar, Hitesh; Mandia, Kabir; Zunaid, M.; Ansari, N.A.; Husain, A.
Highlights: This paper investigates Non-Newtonian flow in a blood artery with two stenosis. Initially previous model is validated, and then further research has been executed with same boundary conditions i.e. Non-Newtonian Pulsatile flow. Two cases - stenosis of (1) 20% with pre-existing geometry with stenosis and (2) 80% compression with pre-existing geometry with stenosis. Velocity Profiles at 6 different locations in a single blood artery has been extracted for both cases and did comparative study here. Shear strain rate and velocity contour has been extracted for both cases and their effect has been studied. Abstract: The purpose of this work is to simulate and analyse the movement of blood passing from stenosis of an artery of a person with atherosclerosis artery disease. We used three-dimensional modelling and simulation of blood flow through two arteries consisting of two stenosis each, one with the same radius for both the cases and the other with different radii for each case. The type of blood flow was considered to be simple pulsatile in order to mimic the rhythmic pulses of the human heart. The carreau yasuda model was used for the hemodynamic modeling viscosity of fluid and sst (shear-stress-transport) was used as the numerical model. This study considered blood flow models which is non-newtonian and solved the 3D laminar and unsteady NS Equations to extracted velocity profiles at 6 different locations in a blood vessel and shear strain rate for both cases.